Studying the Willingness to Pay for University Librarians' Services: Case Study of Kermanshah University of Medical Sciences - Sara Bahrami Nia; Mahmoud Moradi (بازیابی دانش و نظام‌های معنایی, 2019)
Abstract Purpose: The purpose of this study was to identify the average willingness to pay for the services of Kermanshah Medical Libraries and its effective factors.Methodology: The present study is based on a survey method and conditional valuation, which is part of the preferred method of reporting, to determine the willingness to pay. The research population of all users of Kermanshah University of Medical Sciences libraries was 7470 people. The sample was 553 people based on Michel and Carson's formula. A simple random sampling method was used to select the sample. The data gathering tool was a two-dimensional questionnaire. cronbach's alpha (0.86) was used to determine the reliability. Data analysis was done using statistical methods such as descriptive statistics and nonparametric logistic regression test using simultaneous input of variables.Findings: The average annual willingness of users to use the services of medical science libraries was 20600 toman. Also, the results showed that the education variable had a positive and significant effect on the willingness to pay the users. From the perspective of users, among the various resources and services of medical libraries, books and publications, online databases, offline databases and theses of first rank are other services, which will be worth the cost.Conclusion: The results of this study showed that users are willing to pay annual or monthly amounts to maintain the current services of medical university libraries. It can be said that if paying money would improve the services and change the current situation of the library, It is clear that according to the view of users, higher economic value and, consequently, the willingness to pay for a variety of resources and services of academic libraries will increase significantly.